2008
DOI: 10.1002/j.2048-7940.2008.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Special Approaches for Safe Handling of Disabled Children in the Netherlands

Abstract: This article illustrates the manner in which care providers and lawmakers in The Netherlands are addressing safe patient handling of disabled children. Standardization of ergonomic practices for safe patient handling of children requires tailored solutions at both the ward and the individual patient level. Elements such as physical contact versus device-assisted transfer, healing environment, and nonverbal (or haptonomic) communication should all be taken into accountfor a program to be successful. Experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…The actual use of ergonomic devices in this study may, therefore, be higher than in a random sample of nursing homes and hospitals. However, information from national surveys in 2008 showed that 85% of nursing homes have employed ergocoaches on wards 26. Information from national surveys among hospitals in 2005 showed that ergocoaches were present in 56% of the hospitals, having increased from less than 10% in 2001 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual use of ergonomic devices in this study may, therefore, be higher than in a random sample of nursing homes and hospitals. However, information from national surveys in 2008 showed that 85% of nursing homes have employed ergocoaches on wards 26. Information from national surveys among hospitals in 2005 showed that ergocoaches were present in 56% of the hospitals, having increased from less than 10% in 2001 17.…”
Section: Discussionmentioning
confidence: 99%
“…However, information from national surveys in 2008 showed that 85% of nursing homes have employed ergocoaches on wards. 26 Information from national surveys among hospitals in 2005 showed that ergocoaches were present in 56% of the hospitals, having increased from less than 10% in 2001. 17 This suggests that the results of this study correctly reflect the situation in Dutch nursing homes and hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A thin layer of wood was sliced off from each core using a core microtome [ 28 ] to highlight the tree-rings and allow for the inspection of reaction wood and other abnormal properties. Ring widths were measured to the nearest 0.01 mm using the TimeTable measuring device interfaced with PAST4 software [ 29 ] and an Olympus SZ51 stereomicroscope. Individual tree-ring series were visually cross-dated using the pattern of wide and narrow rings [ 30 ] and verified using the PAST4 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ring widths were measured to the nearest 0.01 mm using the TimeTable measuring device interfaced with PAST4 software [ 29 ] and an Olympus SZ51 stereomicroscope. Individual tree-ring series were visually cross-dated using the pattern of wide and narrow rings [ 30 ] and verified using the PAST4 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patient handling tasks are repetitious in nature and require bending, twisting, and flexing in awkward positions (Collins et al., ; Knibbe, Knibbe, & Crist, ). Current evidence suggests that these repetitious movements exert more strain on muscles and the spine than a static load; therefore, the NIOSH recommended guideline of 35 pounds is in question because it based on a static load while nursing activities are dynamic in nature.…”
Section: Gaps In Knowledgementioning
confidence: 99%